Rapid implementation of a modular clinical trial informatics solution for COVID-19 research. (2021) - Dhond, Rupali; Acher, Ryan; Leatherman, Sarah; Page, Sarah; Sanford, Randolph; Elbers, Danne; Meng, Frank; Ferguson, Ryan; Brophy, Mary T.; Do, Nhan V.
Abstract: Veterans Health Administration (VHA) services are most frequently used by patients 65 years and older, an age group that is disproportionally affected by COVID-19. Here we describe a modular Clinical Trial Informatics Solution (CTIS) that was rapidly developed and deployed to support a multi-hospital embedded pragmatic clinical trial in COVID-19 patients within the VHA. Our CTIS includes tools for patient eligibility screening, informed consent tracking, treatment randomization, EHR data transformation for reporting and interfaces for patient outcome and adverse event tracking. We hope our CTIS component descriptions and practical lessons learned will serve as a useful building block for others creating their own clinical trial tools and have made application and database code publicly available.